Effect of habb-e-quqaya in shaqeeqa (migraine without aura) – An open label clinical trial - Mohd Riyazuddin; Arisha Shahid; Mansoor Ahmad Siddiqui (Journal of Ayurveda, 2021)
Backgrounds: Migraine is a form of primary headache, manifested by the recurrent attacks of pulsating headache, mostly associated with nausea, vomiting, photophobia, and phonophobia, with or without an aura. Its onset is unilateral with varying intensity, frequency, and duration. It is the second-most common cause of headache disorder affecting about 12% of general population with 15% females and 6% males. The World Health Organization listed migraine as the 19th disability cause worldwide. In the present scenario of high prevalence and limited treatment options, this study was conducted to assess the safety and efficacy of a unani formulation named Habb-e-Quqaya, as a nervine tonic, brain tonic, stomachic, purgative, and its action in evacuating viscid morbid matter from the body in the management of migraine without aura. Methods: Thirty patients with migraine without aura were selected and administered with Habb-e-Quqaya 3 tablets weighing 500 mg each twice daily for 45 days. Subjective and objective parameters were assessed for each patient every 15 days. Data were analyzed statistically using the Student's t-test and paired proportion test. Results: Highly significant improvement (P < 0.001) was observed in all subjective and objective parameters. Conclusion: It was thus concluded that Habb-e-Quqaya can be a potential treatment for Shaqeeqa (Migraine without aura) with high efficacy and safety and without any side effects or toxicity during or after the trial. Hence, this study validates the use of Habb-e-Quqaya in Shaqeeqa (migraine without aura).